Heterostructures of CdSe Quantum Dots and g-C3N4 Applied as Electrochemiluminescent Probes for the Detection of Hydrogen Peroxide in Human Serum - Carrillo Palomino, Roodney Alberto (2025)
In this work, we developed a highly sensitive and reproducible electrochemiluminescent sensor based on a heterostructure of cadmium selenide quantum dots capped with 3-mercaptopropionic acid (MPA) + 3-morpholinoethanesulfonic acid (MES) (QDs CdSe) and carbon nitride nanosheets (g-C3N4) for the detection of H2O2 in lyophilized serum samples. To enhance the sensor sensitivity, g-C3N4 nanosheets were utilized as a platform to immobilize the QDs CdSe. An exhaustive characterization of the heterostructure was conducted, elucidating the interaction mechanism between QDs CdSe and g-C3N4. It was revealed that g-C3N4 acts as a hole (h+) donor, while QDs CdSe act as energy acceptors in a resonance energy transfer process, with the electrochemiluminescence emission originating from the QDs CdSe. The electrochemiluminescence intensity decreases in the presence of H2O2 due to the deactivation of the excited states of the QDs CdSe. This electrochemiluminescent sensor demonstrates exceptional performance for detecting H2O2 in aqueous systems, achieving a remarkably low limit of detection (LOD) of 1.81 nM, which is more sensitive than most reported sensors to detect H2O2. The applicability of the sensor was successfully tested where sub-µM levels of H2O2 were accurately quantified. These results highlight the potential of this electrochemiluminescent sensor as a reliable and pre-treatment-free tool for H2O2 detection in biochemical studies and human health applications.